2002
DOI: 10.1093/heapro/17.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion behaviors in Chinese family caregivers of patients with stroke

Abstract: The purpose of this study was to explore the relationship between and among the caregiver's personal factors, the care recipient's functional status, the caregiver's perceived self-efficacy, social support, reactions to caregiving, and health promotion behaviors in family caregivers of community-dwelling stroke patients in Taiwan. A structured home-interview survey methodology was used to collect data from 134 primary caregivers responsible for care of stroke patients in Taipei, Taiwan. The study results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 43 publications
3
39
0
7
Order By: Relevance
“…A family caregiver is defined as anyone who provides unpaid physical and emotional care to an ill or disabled loved one at home including parents, children, spouses, as well as neighbours and friends 2,3 . Tang and Chen 4 show that there has been an increase in health risks among family caregivers which influences their well-being and quality of life. These health risks have been identified as influencing the family caregivers' role and include social isolation, lack of knowledge, limited skills, personal coping styles, stress, depression, anxiety, poor sleeping habits and physical health complications 2,4,5,6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A family caregiver is defined as anyone who provides unpaid physical and emotional care to an ill or disabled loved one at home including parents, children, spouses, as well as neighbours and friends 2,3 . Tang and Chen 4 show that there has been an increase in health risks among family caregivers which influences their well-being and quality of life. These health risks have been identified as influencing the family caregivers' role and include social isolation, lack of knowledge, limited skills, personal coping styles, stress, depression, anxiety, poor sleeping habits and physical health complications 2,4,5,6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Tang and Chen 4 show that there has been an increase in health risks among family caregivers which influences their well-being and quality of life. These health risks have been identified as influencing the family caregivers' role and include social isolation, lack of knowledge, limited skills, personal coping styles, stress, depression, anxiety, poor sleeping habits and physical health complications 2,4,5,6,7,8,9 . Caring for older adults with chronic diseases can also result in occupational imbalance as a result of family, career, and care giving demands 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Supportive psychotherapy other than psychoeducation can also be helpful to caregivers. [4] Instilling and maintaining hope is an important issue to be included in psychotherapy sessions. Groups that would provide support to the caregivers of stroke patients could be organized, similar to groups formed for the families of Alzheimer patients and others.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke creates a crisis, especially for family members who provide primary care for the patient, and anxiety, depression, and burnout syndrome can frequently be observed in these caregivers if there is no intervention. [3,4] This study was an evaluation of the level of anxiety, depression, and burnout in caregivers of stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Tang et al (25) on Chinese family caregivers of patients with stroke showed that perceived social support had a direct and positive correlation with such individuals' lifestyle. The study by Taechaboonsermsak et al (24) on females with cervical cancer and under treatment with radiation therapy evaluated a variety of emotional, information and instrumental supports and reported overall correlation between healthpromoting behavior and support.…”
Section: Discussionmentioning
confidence: 99%